ASSESSMENT OF RAINWATER TREATMENT PERFORMANCE BY AN INTEGRATED RAINWATER HARVESTING SYSTEM - SAMBAS, NURUL FARADILA (2020)
In Malaysia, although the country is suitable to practice rainwater harvesting (RWH) system, its implementation as an alternative water resource remains unrecognised. The quality of the harvested rainwater is still poor for consumption, and the study on the innovation of the RWH system is still insufficient, specifically on the hydraulic context. The present study evaluated the performance of an innovation towards the technology, known as the integrated RWH system, incorporating a few hydraulic components (double first flush (FF) diverters and a custom-designed vortex filter) and a thermostat heater in a dual-part storage tank for a simple mild heat treatment to enhance the harvested rainwater quality.